Precision Frequency Measurement for He-Ne/ I2 Laser Emission with kHz- Accuracy - Thang, Le Huu; Thu, Bui Quoc; Xuan, Vu Khanh; Suh, Ho Suhng; Hoi, Pham Van (Communications in Physics, 2012)
An accurate and precise frequency measurement of S.I. unit traceability is essential not only in the field of frequency metrology but also in many fundamental scientific researches, because an accurate and precise frequency will be able to provide stable reference frequency related quantities like length and time -- the two important elements of physics. In this paper we present our frequency measurement for laser emission of the He-Ne/I2 laser system at the kHz accuracy and precision level. A frequency beat measurement of the laser under test with the standard frequency from a frequency optical comb is conducted. The second measurement method based on the heterodyne technique, where the beats between the hyperfine frequencies of 127I2 isotope at frequency of 474 THz and the testing He-Ne laser frequency recorded. The measurement data from different measurement techniques show a good consistency and therefore the given data are reliable.